1998
DOI: 10.1161/01.hyp.32.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shift Work and Race/Ethnicity on the Diurnal Rhythm of Blood Pressure and Catecholamines

Abstract: Abstract-To evaluate the effects of shift work and race/ethnicity on the diurnal rhythm of blood pressure and urinary catecholamine excretion of healthy female nurses, 37 African American women and 62 women of other races underwent ambulatory blood pressure monitor and urine collection for 24 hours that included a full work shift: day shift (nϭ61), evening shift (nϭ11), and night shift (nϭ27). Awake and sleep times were evaluated from subjects' diaries. Of African Americans, 79% who were working evenings or ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 35 publications
9
86
0
2
Order By: Relevance
“…Several risk factors were exacerbated by night-shift work. [3][4][5][6][7][8] However, elimination of night-shift work is unlikely to be possible for most medical staff, although reduction in the frequency and duration of shifts is recommended. 1,21 Aromatherapy is a relatively inexpensive way to reduce anxiety that does not involve side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk factors were exacerbated by night-shift work. [3][4][5][6][7][8] However, elimination of night-shift work is unlikely to be possible for most medical staff, although reduction in the frequency and duration of shifts is recommended. 1,21 Aromatherapy is a relatively inexpensive way to reduce anxiety that does not involve side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Night-shift work disrupts the normal biological and/or social diurnal rhythms, which are factors in cardiovascular disease, 1,2 as well as in a widening variety of other chronic diseases, including glucose intolerance, 3,4 hypertension 5,6 and depression. 7,8 Endothelium function, which is strongly associated with the onset and development of cardiovascular disease and its risk factors, [9][10][11] has been shown to be impaired after night-shift work.…”
Section: Introductionmentioning
confidence: 99%
“…Yamasaki et al 10 suggested that more night shift workers than day workers are as non-dippers, probably because the quality of sleep was impaired by shift work, and sleep deprivation may induce high nocturnal BP. 10,13 Unfortunately, they did not obtain reports of sleep quality from their subjects.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…10,13 Unfortunately, they did not obtain reports of sleep quality from their subjects. In our study, the quality of sleep did not differ between NS I and NS II, although, according to their diaries, night-shift work impaired the quality of sleep in comparison with day-shift work.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation